Study on the Mixed Materials Proportion of Stratum Based on the Modelling Experiment - Yijun Zhou; Tao Xu (Advances in Civil Engineering)
It is highly significant to select similar materials as well as the proportion of mixed materials in the model test. The mixed materials are used to simulate the stratum of the model test, including the iron ore powder, natural sands, gypsum, and lime. The stratum contains silty clay and silt soil. First of all, the symmetry coefficient of model mechanics parameters are calculated by the equation, and the symmetry ratio is 16 : 1. Second, calculate the proportion of compositions in mixed materials by the orthogonal test. The deviation method is used to analyze the mixed materials and how to influence the elastic modulus, cohesion, and friction angle. Finally, get the mixed materials which meet the symmetry theory and control factors.